Review of Tumidiclava Girault (Hymenoptera: Trichogrammatidae) from Xingjiang, China, with description of two new species and taxonomic notes on other Holarctic taxa - Aishan, Zhulidezi; Triapitsyn, Serguei V.; Hu, Hong-Ying (Zootaxa, 2015)
Four species of Tumidiclava Girault are recorded from Xinjiang Uyghur Autonomous Region, China. Two new species, T. buerjinica Triapitsyn & Aishan sp. nov. and T. tamariska Hu & Aishan sp. nov., are described; the former is also known from Turkmenistan and the latter from Israel. One Palaearctic species, T. subcaudata Nowicki, is newly recorded from China, and a key to females of the Chinese species is given. Taxonomic notes and illustrations are provided on these and also other described taxa of Tumidiclava from the Holarctic region, both sexes of which are keyed including the type species of the genus, T. pulchrinotum Girault (USA), whose male is newly described. Lectotypes are designated for Orthoneura bimaculata Blood & Kryger, 1928 and T. (Orthoneurella) minuscula Nowicki, 1940 and a neotype is designated for Orthoneura bimaculata Blood, 1923.